Effect of powder compaction on radiation-thermal synthesis of lithium-titanium ferrites; IOP Conference Series: Materials Science and Engineering; Vol. 168 : Radiation-Thermal Effects and Processes in Inorganic Materials (RTEP2016) - Surzhikov A. P. Anatoly Petrovich; Lysenko E. N. Elena Nikolaevna; Vlasov V. A. Vitaliy Anatolievich; Malyshev A. V. Andrei Vladimirovich; Korobeynikov M. V.; Mikhailenko M. A. (Technologies and equipment for their implementation, 2017)
Title screen